The Economics of the Enterprise for ASEAN Initiative - Naya, Seiji (Book collections on Project MUSE., 2005)
The Enterprise for ASEAN Initiative (EAI), as envisaged in 2002 by the Bush administration, is set to be a landmark in U.S.-ASEAN trade relations. This study provides a detailed background and a map to the unfolding negotiations. It includes: a detailed review of the U.S.-ASEAN economic relationship, beginning with coverage of the U.S.-ASEAN trade in goods globally and ending with an in-depth analysis of the changing structure of bilateral trade in services; reviews of theories of FTAs and empirical testing of the economics of the EAI itself. Using the USSFTA as a reference point, this study id.